Processing speed predicts SuperAging years later - Ticha, Zuzana; Georgi, Hana; Schmand, Ben; Heissler, Radek; Kopecek, Miloslav (BMC psychology, 2023)
BACKGROUND: SuperAging is one of the current concepts related to elite, resilient or high-functioning cognitive aging. The main aim of our study was to find possible predictors of SuperAgers (SA). METHODS: Community-dwelling older persons (N = 96) aged 80-101 years in 2018 were repeatedly tested (year 2012 and 2018). SA were defined based on their performance in 2018 as persons of 80+ years of age who recalled ≥ 9 words in the delayed recall of the Philadelphia Verbal Learning Test, and had a normal performance in non-memory tasks [the Boston Naming Test, the Trail Making Test Part B, and Category Fluency ("Animals")], which was defined as a score within or above one standard deviation from the age and education appropriate average. Three composite scores (CS; immediate memory, processing speed, and executive functions) were created from the performance in 2012, and analysed as possible predictors of SA status in 2018. RESULTS: We identified 19 SA (15 females) and 77 nonSA (42 females), groups did not significantly differ in age, years of education, and sex. The logistic regression model (p = 0.028) revealed three predictors of SA from the baseline (year 2012), including processing speed (p = 0.006; CS-speed: the Prague Stroop Test-Dots and the Digit Symbol Substitution Test), sex (p = 0.015), and age (p = 0.045). CONCLUSIONS: Thus, SA may be predicted based on the level of processing speed, which supports the hypothesis of the processing speed theory of healthy aging.
Keywords: rychlost zpracování; Aging; kognitivní poruchy; Superagers; Stroop Test; Executive Function; exekutivní funkce; Healthy; Neuropsychological Tests; Processing Speed; kognice; lidé; ženské pohlaví; Humans; Cognition Disorders; neuropsychologické testy; Female; Cognition; Stroopův test